2014
DOI: 10.1177/0003319714545342
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Collateral Circulation and Cardiovascular Risk Factors

Abstract: We sought to determine the association of major cardiovascular risk factors and other comorbidities with the presence or absence of coronary collateral (CC) circulation. All electronic medical records from 2010 to 2011 were retrospectively reviewed. A total of 563 patients were divided into 2 groups: CC present (180) and CC absent (383). Smoking (P = .012, odds ratio [OR] 1.58), hypercholesterolemia (P = .001, OR 2.21), and hypertension (P = .034, OR 1.75) were associated with the presence of CC. Increasing bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…In addition, although there was no between-group differences in the presence of hyperlipidaemia, levels of both LDL and HDL were significantly higher in the GC group. Elevated HDL and hypercholesterolemia were previously shown to be associated with good collateral development [39,40]. Our findings are consistent with these data.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, although there was no between-group differences in the presence of hyperlipidaemia, levels of both LDL and HDL were significantly higher in the GC group. Elevated HDL and hypercholesterolemia were previously shown to be associated with good collateral development [39,40]. Our findings are consistent with these data.…”
Section: Discussionsupporting
confidence: 93%
“…Some investigators have found that smoking was associated with well-developed coronary collateral circulation which might alleviate myocardial ischemia and necrosis when epicardial coronary arteries were occluded. [ 3 , 4 ] Well-developed coronary collateral circulation usually results in fewer infarct size, improved cardiac function, and fewer mortality. [ 5 7 ] Smoking improves coronary collateral circulation which may partial explain the so-called smokers’ paradox.…”
Section: Introductionmentioning
confidence: 99%
“…Except from smoking, other cardiovascular risk factors such as hypertension, diabetes mellites also have some impacts on coronary collateral circulation. [ 3 ] Yetkin et al [ 9 ] found that diabetes mellitus was an independent factor for rarefaction of coronary collateral circulation. However, the study by Niccoli et al [ 10 ] found that patients with diabetes mellitus had better collateral development compared with nondiabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Additionally, studies showed that hypertension, obesity, DM, dyslipidemia, and cigarette smoking are also associated with coronary collateral development. [17][18][19][20] Endogenous mediators, including apelin, NLR, mean corpuscular volume, monocyte count, high sensitive C reactive protein, adhesion molecules, and growth factors were shown to be related with coronary collateral development. [21][22][23][24] Additionally, Liu et al showed that CCC development is associated with race and sex.…”
Section: Discussionmentioning
confidence: 99%